2008
DOI: 10.1177/089686080802800307
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis in Peritoneal Dialysis Patients in Uruguay

Abstract: Uruguay is a South American country (3241003 inhabitants) where renal replacement treatment is universally available. The aim of this study was to analyze the incidence and outcome of peritonitis, and the causative organisms and their sensitivity, in order to recommend an empiric initial antibiotic treatment. A retrospective descriptive study of all peritonitis during the period 2004 – 2005 was performed (144 peritonitis, 44% due to gram-positive bacteria). We conclude that the high prevalence of methicillin-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Peritonitis was the major complication in this study. As in the literature, coagulase-negative staphylococcus was the most common agent despite the use of a twin-bag system to reduce bag exchange-related external contamination (16). The peritonitis rate in our program was 1 episode per 57.79 patient-months.…”
Section: Discussionmentioning
confidence: 56%
“…Peritonitis was the major complication in this study. As in the literature, coagulase-negative staphylococcus was the most common agent despite the use of a twin-bag system to reduce bag exchange-related external contamination (16). The peritonitis rate in our program was 1 episode per 57.79 patient-months.…”
Section: Discussionmentioning
confidence: 56%
“…Peritonitis rates have been used in the quality evaluation of PD programs (32-34). In Uruguay, a national registry of PD infections (active since 2004) demonstrated that the main causative micro-organism is methicillin-resistant CNS; the national overall peritonitis rate is 0.5 episodes/patient–year (35). In the present study, the overall peritonitis rate showed significant improvement in the 2 years after the PDEP began compared with the 2 years before, declining to 0.28 episodes/patient–year from 0.55 episodes/patient–year.…”
Section: Discussionmentioning
confidence: 99%
“…La peritonitis relacionada con la diálisis peritoneal (DP) es una de las principales causas del fracaso de la técnica [1][2][3] . Desde el año 2004 el Grupo de Estudio de Diálisis Peritoneal de la Sociedad Uruguaya de Nefrología lleva un registro de todos los episodios de peritonitis del país, con el objetivo de adecuar el protocolo antibiótico empírico inicial a los gérmenes prevalentes y su perfil de sensibilidad 4,5 . En Uruguay, la incidencia es 0.33 peritonitis/paciente-año 6 .…”
Section: Introductionunclassified